2010
DOI: 10.1007/s00256-010-0939-8
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-induced autologous chondrocyte implantation of the knee: mid-term and long-term follow-up by MR arthrography

Abstract: Magnetic resonance arthrography improved the evaluation of implants and facilitated the characterisation of MACI integration with contiguous tissues. The follow-up showed significant changes in MACI, even at 60 months, allowing for useful long-term MR evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 45 publications
8
74
1
Order By: Relevance
“…Variations on ACI, such as matrix‐assisted chondrocyte implantation (MACI), where cells are seeded or expanded on a scaffold prior to implantation, have also been in clinical use for a number of years. MRI assessment of cartilage repair has revealed a more hyaline‐like zonal architecture following MACI compared to microfracture (Welsch et al , 2008) and recent studies have also highlighted advantages of MACI compared to ACI (Basad et al , 2010; Genovese et al , 2010). However, the repair tissue found with both procedures is still at best hyaline‐like (Getgood et al , 2009a, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Variations on ACI, such as matrix‐assisted chondrocyte implantation (MACI), where cells are seeded or expanded on a scaffold prior to implantation, have also been in clinical use for a number of years. MRI assessment of cartilage repair has revealed a more hyaline‐like zonal architecture following MACI compared to microfracture (Welsch et al , 2008) and recent studies have also highlighted advantages of MACI compared to ACI (Basad et al , 2010; Genovese et al , 2010). However, the repair tissue found with both procedures is still at best hyaline‐like (Getgood et al , 2009a, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…MRA did not reveal any irregularities of the articular surface and showed good integration of the cartilage of the oCD fragment with the surrounding tissue. We used MRA because it can show the presence of minimal clefts between the oCD fragment and the condyle and between the osteochondral plugs and the surrounding cartilage, otherwise no evident at standard MR (15). in all cases the arthroscopic evaluation confirmed the type and size of the lesions highlighted by MRA.…”
Section: Discussionmentioning
confidence: 92%
“…the "unit 2" protocol consisted of 3D isotropic t1 sequences in the axial plane; sagittal and coronal tsE t1 sequences; and sagittal or coronal fat-saturated FsE PD/t2 sequences. An independent observer (GA), blinded to the surgical treatment, evaluated the MRA findings using the modified MoCARt scoring scale (15).…”
Section: Surgical Technique and Rehabilitation Protocolmentioning
confidence: 99%
“…Genovese et al performed MR arthrography on13 patients with a total of 15 matrix-induced autologous chondrocyte implantation grafts 30 and 60 months following implantation. 2 The grafts were evaluated using the modified Magnetic Resonance Observation of Cartilage Repair Tissue (MOCART) scoring scale, which was compared with validated clinical scores. 2 They found a relationship between the MR and clinical scores at both follow-up intervals and concluded that MR arthrography is a useful tool for long-term follow-up in this setting.…”
Section: Autologous Chondrocyte Implantsmentioning
confidence: 99%